Interval oscillation of a second order nonlinear differential equation with a damping term - Rogovchenko, Yuriy V.; Tuncay, Fatoş (My University, 2007)
Using generalized Riccati transformations, we derive new interval oscillation criteria for a class of second order nonlinear differential equations with damping. Our theorems prove to be efficient in many cases where known results fail to apply.
Keywords: Asymptotic behavior; Damping term; Interval oscillation; Nonlinear differential equations; Oscillatory solutions; Second order